2018
DOI: 10.1002/eat.22962
|View full text |Cite
|
Sign up to set email alerts
|

A systematic scoping review of diagnostic validity in avoidant/restrictive food intake disorder

Abstract: Objective Avoidant/restrictive food intake disorder (ARFID) was introduced as a new diagnosis in the DSM‐5. This systematic scoping review explores how ARFID as a diagnostic entity is conceptualized in the research literature and evaluates the diagnostic validity according to the Feighner criteria. Method A systematic scoping review of papers on ARFID in PubMed/MEDLINE and Web of Science was undertaken, following PRISMA and Joanna Briggs Institute guidelines. Results Fifty‐one original research publications, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 109 publications
3
39
0
Order By: Relevance
“…The diagnostic coding proposed by Kurz et al (2015Kurz et al ( , 2016 required the following EDY-Q items to be reported at least often (≥4): (disinterest in food OR sensory food avoidance OR fear of choking) and underweight problems, while weight and shape concern had to be reported less than sometimes (<3). In addition, a broad symptom definition by Schmidt et al (2018) was reported in the supplement due to the fact that ARFID was found to be characterized by other restrictive eating behaviours as well (APA, 2013;Strand, von Hausswolff-Juhlin, & Welch, 2019). This latter definition of broad symptoms of ARFID additionally considered that general or emotional food avoidance, picky eating, avoidance to try new foods, or fear of swallowing could be reported at least often (≥4).…”
Section: Symptoms Of Arfid In the Inpatient And General Population-mentioning
confidence: 99%
“…The diagnostic coding proposed by Kurz et al (2015Kurz et al ( , 2016 required the following EDY-Q items to be reported at least often (≥4): (disinterest in food OR sensory food avoidance OR fear of choking) and underweight problems, while weight and shape concern had to be reported less than sometimes (<3). In addition, a broad symptom definition by Schmidt et al (2018) was reported in the supplement due to the fact that ARFID was found to be characterized by other restrictive eating behaviours as well (APA, 2013;Strand, von Hausswolff-Juhlin, & Welch, 2019). This latter definition of broad symptoms of ARFID additionally considered that general or emotional food avoidance, picky eating, avoidance to try new foods, or fear of swallowing could be reported at least often (≥4).…”
Section: Symptoms Of Arfid In the Inpatient And General Population-mentioning
confidence: 99%
“…The recovery rate of the ARFID group was significantly higher than that of the AN‐R group. In comparison to their Western counterparts, (Strand, von Hausswolff‐Juhlin, & Welch, 2018), these Japanese patients with ARFID were more likely to be women, and experienced better treatment outcomes.…”
Section: Resultsmentioning
confidence: 88%
“…Of course, a heterogeneous symptomatology that lacks specificity may simply reflect different ways in which a single underlying dysfunction is expressed. At present, there is a paucity of research into ARFID, due to its relatively recent inclusion in DSM-5 (Strand et al 2019). However, ARFID can be present alongside other mental disorders such as ASD, ADHD, intellectual disability, and reactive attachment disorder.…”
Section: The Dysfunction Requirement and Fdsmentioning
confidence: 99%